Predator mite application methods for biological control of twospotted mites in hops - Shaw, P.W.; Wallis, D.R. (New Zealand Plant Protection, 2007)
The efficacy of a novel air stream predator mite application method for the control of twospotted mites (TSM Tetranychus urticae) in hops was compared with a standard teaspoon release method Predator mites (Phytoseiulus persimilis) were successfully established with a single release using both application methods and TSM declined to low numbers during the monitoring period Application of predator mites with a delivery device attached to a conventional leaf blower mounted on a quad bike was equally effective and at least four times faster than hand application There was no evidence of any physical damage to mites applied with the mite blower device The potential of the air stream application method to improve the efficiency of biological control of TSM using predator mites is discussed